2018
DOI: 10.1089/mdr.2016.0096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CTX-M-ProducingKlebsiellaspp. in Broiler, Kuroiler, and Indigenous Poultry in West Bengal State, India

Abstract: This study was undertaken to detect the prevalence of CTX-M-producing Klebsiella spp. in healthy broiler, indigenous, and kuroiler birds reared in West Bengal (India) during November 2014-February 2015. In addition to CTX-M gene, the study was also conducted to reveal the occurrence of other β-lactamase and class I integron genes in Klebsiella spp. isolates along with their clonal relationship. A total of 321 cloacal swabs from healthy broiler, indigenous, and kuroiler birds were collected from different place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Resistance against antimicrobials leads to limited therapeutic options, resulting in increasing difficulties of treatments. In contrast to ESBL- producing E. coli which have become very common in veterinary medicine, especially in livestock, companion animals and wildlife, ESBL-producing K. pneumoniae were detected rarely in healthy broiler (Hiroi et al, 2012 ; Yossapol et al, 2017 ; Mahanti et al, 2018 ), diseased horses (Vo et al, 2007 ) dairy cows (Locatelli et al, 2010 ) and in companion animals (Ewers et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance against antimicrobials leads to limited therapeutic options, resulting in increasing difficulties of treatments. In contrast to ESBL- producing E. coli which have become very common in veterinary medicine, especially in livestock, companion animals and wildlife, ESBL-producing K. pneumoniae were detected rarely in healthy broiler (Hiroi et al, 2012 ; Yossapol et al, 2017 ; Mahanti et al, 2018 ), diseased horses (Vo et al, 2007 ) dairy cows (Locatelli et al, 2010 ) and in companion animals (Ewers et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle manure is widely used as biological fertilizer, which increases the chance of environmental dissemination of ESBLs from a fecal source. Separate studies conducted by our group revealed the presence of ESBLs in broilers or birds kept exclusively for meat (81,82) but not in backyard poultry reared by a large section of resource-poor farmers in India (83). Likewise, ESBLs and ACBLs were frequently detected in poultry from the developing countries of Asian (84,85), African (86), and European (87) regions.…”
Section: Cephalosporin Resistant Bacteriamentioning
confidence: 87%
“…Antibiotic resistance can develop for a variety of reasons, including the length of antibiotic use (Moini et al, 2015). Antibiotic misuse has resulted in a global antibiotic resistance epidemic (Bartlett et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The CTXM gene is produced by K. pneumoniae, an extended-spectrum β-lactamase (ESBL) generating bacteria. This gene can be passed down directly and indirectly (Mahanti et al, 2018). Resistant Gram-negative and Gram-positive bacteria will be difficult to treat, if not impossible to treat, with antimicrobials (Akova, 2016).…”
Section: Introductionmentioning
confidence: 99%